Clues to recognition of fumarate hydratase‐deficient renal cell carcinoma: Findings from cytologic and limited biopsy samples1. Issue 12 (19th October 2018) - Shyu, Irene; Mirsadraei, Leili; Wang, Xiaoyan; Robila, Valentina; Mehra, Rohit; McHugh, Jonathan B.; Chen, Ying‐Bei; Udager, Aaron M.; Gill, Anthony J.; Cheng, Liang; Amin, Mahul B.; Lin, Oscar; et al.
Abstract : Background: Fumarate hydratase (FH)‐deficient renal cell carcinoma (RCC) is rare and highly aggressive and is believed to arise mostly in the setting of hereditary leiomyomatosis‐RCC syndrome with a germline mutation of FH . Because of the aggressiveness of these tumors and a frequent lack of ascertainable family history, these tumors may first present as metastases and be sampled by cytology. The cytologic findings of FH‐deficient RCC have not previously been reported. Methods: Cytologic and limited biopsy samples from patients with FH‐deficient RCC were reviewed retrospectively. Results: In total, 24 cytologic and limited biopsy samples from 19 patients (6 women and 13 men; age range, 22‐69 years) who had FH‐deficient RCC and metastasis at presentation were evaluated. These included 21 cytology samples ranging from malignant effusions (n = 7) to metastases (n = 11), to samples of primary kidney tumors (n = 3). The samples exhibited cells, often in clusters and abortive papillae, with voluminous, finely vacuolated cytoplasm and large, pleomorphic nuclei with prominent, viral inclusion‐like nucleoli. A distinctive finding of peripheral cytoplasmic clearing frequently was apparent, and intranuclear cytoplasmic pseudoinclusions were less frequent. Of 7 cell block and biopsy samples, several of which represented sampling from the same patient, all demonstrated tissue fragments that had discernable morphologic patterns associated with FH‐deficient RCC, including tubulocystic and intracystic papillary growth. Conclusions: Features characteristic and suggestive of FH‐deficient RCC may be identified in cytologic and small biopsy samples. Although the current samples were identified retrospectively in well characterized cases of FH‐deficient RCC, the authors argue that, with appropriate clinical correlation, these features are sufficiently distinctive to trigger recognition and confirmatory workup. Abstract : Features suggestive of fumarate hydratase‐deficient renal cell carcinoma may be identified in cytology and small biopsy samples. Cells exhibit large, pleomorphic nuclei with prominent, inclusion‐like macronucleoli and voluminous cytoplasm, often with peripheral cytoplasmic clearing.